Self-Spiritual Healing Therapy on Anxiety Conditions in Diabetes Type II in the Lovina Tourism Area - Made Kurnia Widiastuti Giri (JST (Jurnal Sains dan Teknologi), 2023)
After pandemic, post-acute care is being important to maintain wellness in patient with chronic disease. Diabetes type II (diabetes mellitus) is a degenerative chronic disease whose number of cases is increasing from time to time. This increase is also in line with the increasing interest of individuals in spiritual healing and this spiritual healing method is efficient because it can be done independently and with online tutorials. This study aims to prove the effectiveness of spiritual healing in reducing anxiety levels in diabetes type II patients. This research is Quasi-experimental research (quasi-experimental). A quasi-experiment is an experiment that requires treatment but does not use random assignment in creating comparisons to conclude that there is a change due to treatment. This research in the first year uses quantitative and descriptive qualitative analysis techniques according to the characteristics of the data needed to describe each research problem. Based on the results of data analysis and discussion, it was concluded that anxiety is a condition where our bodies experience feelings of anxiety and restlessness that can arise from the presence of a trigger (stressor). The role of yoga in reducing anxiety in most journals is said to be positively related and proven to have a significant effect.